Ethical leadership as a way to promote work-related well-being - Taatila, Johanna (fi=Turun yliopisto|en=University of Turku|, 2016)
The purpose of this study was to clarify the connections of ethical leadership with the work-related well-being of employees. Additionally, the role of occupational health care in ethical leadership that promotes work-related well- being was analyzed. The objective of the study was to produce knowledge to support the development of ethical leadership and work-related well-being as well as to find ways for occupational health care to support organizations in these actions. The target groups of this study consisted of the managers (N=43) and employees (N=336) working in one organization in the Finnish energy industry. The population was studied in November 2014 using census. The data was gathered with two different web-based surveys containing structured and open questions. The survey for managers consisted of background questions and statements concerning ethical leadership, work-related well-being and occupational health care. The employee questionnaire consisted of questions about background and statements about work-related well-being and ethical leadership. The structured questions were analyzed with SPSS Statistical Program and the open questions using inductive content analysis. At least 80 % of the managers saw their actions as ethical in all but one part of ethical leadership. The work-related well-being of the employees was found best in the area of ability to work (91 % agreed) and lowest in the area of experience of ethical leadership (67 % agreed). The results showed a strong positive connection between ethical leadership and all the components of work- related well-being. The managers and employees were generally quite happy with the services of occupational health care but managers saw some problems with the collaboration with occupational health care. Several ways to improve work-related well-being and collaboration with occupational health care were found. One of the most important things was thought to be offering ways to maintain ability to work and making these actions visible. Investing in ethical leadership and work-related well-being is extremely important for the success of an organization and the societal benefits cannot be forgotten either. The role of occupational health care in promoting the health and well-being of employees is substantial. Occupational health care should offer managers more tools to recognize difficult situations and acting in them as well as encourage managers to seek help from occupational health care without hesitation in problematic situations of leadership.